Calibrated ages without Pb210 of Hanhijanka HAN (H P3) peat core from Finland - Markku Mäkilä (PANGAEA, 2021)
Calibrated ages (without Pb210) of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.